Aluminum phosphide: Toxicological profiles, health risks, environmental impact, and management protocols: A review - Selin Çakmakcı Karakaya; Cavit Işık Yavuz (Turkish Journal of Emergency Medicine, 2025)
Aluminum phosphide (AlP) is a common pesticide known for extremely negative environmental, health, and work-related outcomes. Its high availability and easy accessibility have led it to become the chosen method of suicide in many low- and middle-income countries. When AlP reacts with moisture or water, it releases phosphine gas, which is quickly absorbed by the body and leads to severe toxic effects, even death. Occupational and environmental health risks are particularly high in cases of large-scale fumigation or accidental exposure. In Türkiye, two people, one of whom was a child, died due to AlP accidents that affected workplaces and the environment and caused hospitalizations in 2023. In 2024, further suspected cases have been reported, highlighting the ongoing risk. First responders, particularly emergency department team, paramedics, and firefighters, are at significant risk of exposure when managing these cases. The lack of awareness and appropriate protective measures during initial intervention can lead to secondary exposure, worsening the crisis. Medical staff taking care of victims are also at risk of being exposed, further emphasizing the need for stringent safety precautions. Besides, this pollution might cause irreversible damage to soil and water. Thus, this review provides insight into the physical and chemical properties, mechanism of toxicity, current treatment modalities, health–environmental effects, and preventive measures. Given its high toxicity and frequent usage, increased awareness and preparedness among first responders and healthcare professionals are essential. This is a lesson in practice for better safety protocols and emergency response to mitigate health hazards and environmental impacts.